Pengembangan Sensor Koil Datar 3-D untuk Deteksi Gempa Dini di Wilayah Lombok - Islahudin; Muhammad Nizaar (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
In this study, a flat coil application as a three-dimensional (3-D) vibration sensor for early detection of earthquake is designed to detect earthquakes in Lombok Island. Flat coil is a very thin winding wire and is used as an inductor. When inductance changes, frequency will change as well. The frequency can be converted into voltage to represent the distance. This effect is applied to the low frequency using three-dimensional pendulum (x,y,z) to detect the earthquake in Lombok, West Nusa Tenggara. Lombok Island is a territory that lies between the large plate of Asia and plate of Australia, thus, it belongs to earthquake belt territory. The software of 3-D vibration sensor for early detection of earthquakes uses Atmega 16 microcontroller vibration data acquisition program as a voltage data recorder. Meanwhile, Arduino Nano is used to display the waveform and to calculate the frequency of vibration. Based on the calibration, the frequency of vibrations which can be measured are around 0.468 Hz on the x-axis (source frequency is 0.46 Hz), around 0.55 Hz on the y-axis (source frequency is 0.5 Hz), and around 0.48 Hz on the z-axis (source frequency is 0.5 Hz).